Understanding Chinese Bureaucracy: A Systematic Literature Review - Huang, Qiyi (International Journal of Social Sciences and Public Administration, 2024)
An in-depth study of Chinese bureaucracy and its characteristics is an inseparable research topic in the field of social science in contemporary China. The historical lineage of Chinese bureaucracy shows a development from monarchical bureaucracy to cadre system. The Chinese bureaucratic organization is regarded as a cadre system with Chinese characteristics, characterized by hierarchy, centralization, political loyalty, meritocracy, and personification; the pressure system, administrative contract system, and project system are its operation mechanisms. China's bureaucracy has been transformed from a revolutionary group to a modern bureaucracy, and has now entered a period of adjustment and improvement. Chinese officials pay attention to moral cultivation and character building, and their selection and appointment emphasizes the principles of both virtue and talent, and puts virtue first. The structure of Chinese officials represents a hierarchical pyramid structure, and relationship is the core concept in understanding the interpersonal network of Chinese officials. The emphasis on informatization, transparency, specialization, and innovation is the focus and trend of future research on Chinese bureaucracy.